A review of 50 consecutive cytology cell block preparations in a large general hospital. Issue 12 (December 1997) - Mayall, F; Chang, B; Darlington, A
Abstract : AIMS: To review consecutive cell block preparations of cytological specimens in a large general hospital. METHODS: 50 cell blocks were made over an 18 month period in which about 1900 fine needle aspirations (FNAs) were performed. The aspirator was a cytologist or, for image guided FNAs, a radiologist with a cytologist at hand to collect the specimen. Forty eight cell blocks were from FNAs and two were from serous fluids. RESULTS: The cellularity of the cell blocks was inadequate in only four preparations. The main motive for making cell blocks was to obtain tissue for immunohistochemistry. This was performed on 28 cases and a total of 107 immunostained sections were produced. The most common diagnostic dilemma was between carcinoma and melanoma, and the second most common between carcinoma and lymphoma. Consequently cytokeratin, S-100, and LCA were the most frequently used antibodies. At least one of these three antibodies was positive in 17 cases. Five cases were immunostained only for prognostic breast markers. CONCLUSIONS: The use of cell block immunohistochemistry is a reliable and technically unsophisticated aid in the cytological examination of tumours other than lymphomas. Success depends on having highly experienced aspirators that reliably obtain sufficiently cellular material.